2021
DOI: 10.3389/fcell.2021.647301
|View full text |Cite
|
Sign up to set email alerts
|

CORO6 Promotes Cell Growth and Invasion of Clear Cell Renal Cell Carcinoma via Activation of WNT Signaling

Abstract: Renal cell carcinoma (RCC) constitutes the most lethal type of genitourinary cancer. Understanding of RCC tumor biology helps to identify novel targets and develop directed treatments for patients with this type of cancer. Analysis from both The Cancer Genome Atlas Kidney Renal Clear Cell Carcinoma dataset and our RCC samples demonstrated that the expression level of CORO6 was significantly higher in RCC patients than in normal kidney tissues, and its level was highly associated with tumor stage and grade. Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Additionally, MMP-9 is one of the Wnt pathway target genes, which can be transcriptionally regulated [ 31 ]. According to some substantial studies, the WNT/ β -catenin pathway is hyperactivated in ccRCC, and targeted inhibition of the WNT/ β -catenin pathway may become a feasible therapeutic strategy for tumors [ 32 34 ]. Here, our results showed that NEK2 silencing could obviously downregulate the protein expression levels of key proteins, such as p-GSK-3 β , β -catenin, and the downstream regulator c-Myc, proving that NEK2 silencing could inhibit the WNT/ β -catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MMP-9 is one of the Wnt pathway target genes, which can be transcriptionally regulated [ 31 ]. According to some substantial studies, the WNT/ β -catenin pathway is hyperactivated in ccRCC, and targeted inhibition of the WNT/ β -catenin pathway may become a feasible therapeutic strategy for tumors [ 32 34 ]. Here, our results showed that NEK2 silencing could obviously downregulate the protein expression levels of key proteins, such as p-GSK-3 β , β -catenin, and the downstream regulator c-Myc, proving that NEK2 silencing could inhibit the WNT/ β -catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of WNT was observed in the progression of breast tumors and was associated with tumor drug resistance [ 43 ]. Wang et al [ 44 ] found that activating WNT signaling can promote cell growth and invasion of ccRCC. Colic et al [ 45 ] found that abnormal MAPK signaling transduction can provide therapeutic potential for the treatment of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The salient characteristics of EMT is epithelial markers E-cadherin expression quantity, at the same time N-cadherin interstitial cell marker protein expression and transcription factors related to the rise. EMT can through different signaling pathways such as Notch and Wnt pathways activated, these molecular pathways within cells by transcription factor q and Slug control to induce the occurrence of EMT ( 29 , 30 ). The results showed that ligustrazine could significantly decrease the protein expression of N-cadherin, snail and Slug.…”
Section: Discussionmentioning
confidence: 99%